(untitled) (Journal of Computational Mathematics, 2004)
A modification of classical third order methods is proposed. The main advantage of these methods is that they do not need evaluate any second order Fréchet derivative. A convergence theorem in Banach spaces is analyzed. Finally, some preliminary numerical results are presented.